The publicity handbook - Yale, David R. (Chicago: NTC Business Books., 1991)
Los temas principales de este texto son: Approaching the media: observing format preferences: working withing deadlines: introducing yourself to the media: building your reputation with the media: checklist-basic of good media relations.
Incluye bibliografía
Keywords: Marketing; Publicidad